1992
DOI: 10.1084/jem.176.3.897
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of tumor necrosis factor alpha production in human monocytes by inhibitors of protein phosphatase 1 and 2A.

Abstract: SummaryThe protein phosphatase 1 and 2A inhibitor, okadaic acid, has been shown to stimulate many cellular functions by increasing the phosphorylation state of phosphoproteins. In human monocytes, okadaic acid by itself stimulates tumor necrosis factor c~ (TNF-c~) mRNA accumulation and TNF-c~ synthesis. Calyculin A, a more potent inhibitor of phosphatase 1, has similar effects. TNF-ol mRNA accumulation in okadaic acid-treated monocytes is due to increased TNF-cr mRNA stability and transcription rate. The incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 16 publications
4
17
0
Order By: Relevance
“…Kupffer cells might be especially sensitive to the inhibitory or oxidative stress-mediated effects of OA because we showed that OA concentration in excess of 50 µM, which did not stress other cell types [28], did lead to induction of TNF-␣ mRNA. OA-mediated induction of TNF-␣ mRNA is consistent with previous observations in macrophage systems [29,30]. TNF-␣ mRNA was induced by LPS in the presence of NAC in cells treated with low concentrations of OA that by themselves were innocuous.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Kupffer cells might be especially sensitive to the inhibitory or oxidative stress-mediated effects of OA because we showed that OA concentration in excess of 50 µM, which did not stress other cell types [28], did lead to induction of TNF-␣ mRNA. OA-mediated induction of TNF-␣ mRNA is consistent with previous observations in macrophage systems [29,30]. TNF-␣ mRNA was induced by LPS in the presence of NAC in cells treated with low concentrations of OA that by themselves were innocuous.…”
Section: Discussionsupporting
confidence: 80%
“…If NAC were operating exclusively as a passive antioxidant then one would expect that it would have inhibited the oxidative stress aspects of OA. These results, together with previous studies in other macrophage populations [29,30], may suggest the presence of an alternative signaling pathway that potentially mediates the inactivation of the inflammatory response.…”
Section: Fig 3 Nac Inhibits Nuclear Nf-b Activity (A) While It Doesmentioning
confidence: 48%
See 1 more Smart Citation
“…The specificity of the TNF-␣ response in cardiac cells was assessed by examining the action of agents known to induce TNF-␣ expression in myeloid cells (9,29). As shown in Fig.…”
Section: Effect Of Nf-b Inhibitors and Activators On Tnf-␣ Secretion mentioning
confidence: 99%
“…Protein kinases and phosphatases regulate TNF-␣ gene activity. TNF-␣ gene expression is blocked by tyrosine kinase inhibitors (48) and stimulated by inhibitors of phosphatases 1 and 2A (51). Considering the ability of 2-AP to inhibit splicing of TNF-␣ mRNA from precursor transcripts, we examined the effects of H7 and STS, inhibitors of protein kinases C and A, on PMA-induced TNF-␣ RNA expression ( Fig.…”
Section: -Ap Elicits Accumulation Of Unstable Functional Tnf-␣ Precmentioning
confidence: 99%